PENGARUH GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN PERCETAKAN DIMAS KOTA PALEMBANG - Mohd Kurniawan (JEMBATAN, 2018)
This study aims to determine the effect of leadership style on employee performance in Printing Dimas City Palembang by using questionnaires as much as 52 respondents. It can be concluded that the value of regression coefficient for indicator of autocratic leadership style with value 0,413, democracy with value 0,422 and laise faire with value 0,412 at regression equation show positive value. It can be interpreted that the style of leadership of democracy has greater influence than other indicators. And for the indicator laise faire leadership style has the least influence compared to other indicators. result of hiptesis test of leadership style show significant level 0,001. This significant level is smaller than 0.05, which means that the hypothesis in this study reject Ho and accept Ha.If P value <? = 0.05 then Ha accepted and can be interpreted leadership style has a significant influence on performance. Keywords : leadership and performance